Novel Roles for Chloride Channels, Exchangers, and Regulators in Chronic Inflammatory Airway Diseases - Monica Sala-Rabanal; Zeynep Yurtsever; Kayla N. Berry; Tom J. Brett (Mediators of Inflammation)
Chloride transport proteins play critical roles in inflammatory airway diseases, contributing to the detrimental aspects of mucus overproduction, mucus secretion, and airway constriction. However, they also play crucial roles in contributing to the innate immune properties of mucus and mucociliary clearance. In this review, we focus on the emerging novel roles for a chloride channel regulator (CLCA1), a calcium-activated chloride channel (TMEM16A), and two chloride exchangers (SLC26A4/pendrin and SLC26A9) in chronic inflammatory airway diseases.